Evaluation of tool wear mechanisms and tool performance in machining single-phase tungsten. (January 2021) - Olsson, Mike; Bushlya, Volodymyr; Lenrick, Filip; Ståhl, Jan-Eric
Abstract: Tungsten is commonly used in cemented carbide tooling solutions and as an alloying element in superalloys and steels. In pure form, as a single-phase tungsten, it is used in nuclear and research facilities. Tungsten is known for its poor machinability resulting in excessive tool wear, which puts high requirements on the selected tooling solution. Also, single-phase tungsten is a highly brittle material, thus often leading to surface damage when machining. In this study, eleven different tool materials: ceramics, coated and uncoated cemented carbide, cermet, PcBN and PCD have been tested in longitudinal turning of high purity tungsten (W > 99.9%) in order to identify suitable tool candidates. Seven cutting tool solutions consistently suffered from excessive tool wear or breakage after a few seconds of engagement time. Only two tool materials, PCD and PVD (TiAlN – TiSiN) coated cemented carbide provided sufficient performance. Analysis of their wear mechanisms with scanning and transmission electron microscopy revealed abrasion, oxidation and cracking of WC grains and diffusional dissolution of WC and Co in case of carbide tools. For PCD tools the main identified mechanisms are abrasion and diffusional dissolution. Cracking, formation of build-up edges, presence of workpiece porosity and W adhesion on the machined surface was found to be responsible for poor surface quality and sub-surface damage. Surface roughness for the PCD ranged within R a = 1.3–1.7 μm and for the PVD coated carbide tool R a = 1.0–1.5 μm. Highlights: Adhesion of tungsten on the rake and flank was present and in the form of build-up edges. Wear mechanism of oxidation and cracking of WC grains and diffusional dissolution of WC and Co. The main identified mechanisms for PCD and PcBN are abrasion and diffusional dissolution.